A revision of the Palaearctic Pimeliini (Coleoptera: Tenebrionidae): a comparative analysis and systematic position of Eastern European and Asian taxa with dorso-lateral eyes - Chigray, Svetlana N.; Nabozhenko, Maxim V.; Chigray, Ivan A.; Abakumov, Evgeny V. (European Journal of Taxonomy, 2022)
A taxonomic review of tenebrionid platyopoid genera of the subfamily Pimeliinae from Eastern Europe, Central Asia, Afghanistan, Iran and Pakistan is given. This group of taxa was known before 1994 as the tribe Platyopini Motschulsky, 1849, which is now interpreted as a junior synonym of Pimeliini Latreille, 1802. The group is different from other Pimeliini in having dorso-lateral eyes, located above the level of the genae, and it includes the following ultrapsammophilic genera at least from Central and Southern Asia: Apatopsis Semenov, 1891, Habrochiton Semenov-Tjan-Shansky, 1907, Habrobates Semenov, 1903 [= Kawiria Schuster, 1935 syn. nov.], Dietomorpha Reymond, 1938, Przewalskia Semenov, 1893, Mantichorula Reitter, 1889, Platyope Fischer von Waldheim, 1820 [= Homopsis Semenov, 1893 syn. nov.], Earophanta Semenov, 1903. These genera are distributed in almost all large deserts of Palaearctic Asia: Karakum, Kyzylkum, Muyunkum, Taklamakan, Gobi, Registan, Dasht-e-Kawir, Dasht-e-Lut, as well as in other arid and semi-arid sandy landscapes from European Russia to the south of Eastern Siberia. The group of platyopoid genera is polyphyletic. We propose at least two monophyletic branches: the Habrobates genus group (the first four genera mentioned above), which represents the subtribe Habrobatina Nabozhenko & S. Chigray subtrib. nov. and the Platyope genus group (latter four genera) within the nominotypical subtribe. A new species is described from Pakistan (Balochistan): Dietomorpha gonzalesi S. Chigray & Nabozhenko sp. nov. Platyope granulata Fischer von Waldheim, 1820 is recorded for Kazakhstan for the first time. The following synonymy is resurrected: Apatopsis grombczewskii Semenov, 1890 = Apatopsis conradti Semenov, 1890, syn. resurr. Two new combinations resulting from the synonymy of genera are given: Habrobates gabrieli Schuster, 1935 comb. nov. (from Kawiria), Platyope grumi Semenov, 1893 comb. nov. (from Homopsis). Lectotypes are designated for the following taxa: Apatopsis grombczewskii (Semenov, 1891), Apatopsis conradti Semenov, 1891, Habrochiton vernus Semenov-Tjan-Shansky, 1907, Habrobates vernalis Semenov, 1903, Kawiria gabrieli Schuster, 1935, Platyope dilatata Reitter, 1887; Mantichorula semenowi Reitter, 1889, Mantichorula grandis Semenov, 1893, Homopsis grumi Semenov, 1893, Platyope serrata Semenov, 1893, Platyope planidorsis Reitter, 1889, Platyope tomentosa Semenov, 1893. Additional information for type specimens studied by the authors is given for Habrochiton primaeveris Semenov-Tjan-Shansky, 1907 (holotype), Habrobates vejisovi Kelejnikova, 1977, Platyope ordossica Semenov-Tjan-Shansky, 1907 (holotype), Earophanta autumnalis Semenov, 1903 (holotype, junior synonym of E. planidorsis Reitter, 1889), Earophanta loudoni Semenov, 1903 (holotype, junior synonym of Earophanta pilosissima Reitter, 1895), Earophanta pubescens Skopin, 1960 (holotype, paratypes), Earophanta beludzhistana Bogatchev, 1957 (holotype).